Intracavity Gain Detection Applied to Transient Inversions of IF. Issue 5 (1987) - Williamson, R. L.; Hanko, L.; Davis, S. J.
Abstract : A CW dye laser has been used to study transient optical gain on the B →X electronic transition of iodine monofluoride. By placing the gain generator inside the CW dye laser cavity, gain was readily observed even at levels too small to support lasing in a low loss cavity. Transient phenomena, including V–T energy transfer, were easily observable. An analysis of the intracavity gain detection technique revealed a method for estimating optical gain. The technique should be readily applicable to other systems.